2018
DOI: 10.5152/tud.2018.48742
|View full text |Cite
|
Sign up to set email alerts
|

The role of probiotics in women with recurrent urinary tract infections

Abstract: Ali Serdar Gözen, et al.; Robot-assisted vasovasostomy and vasoepididymostomy: Current status and review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 46 publications
1
37
0
1
Order By: Relevance
“…Development of multi-drug resistance has led doctors to look for milder prophylactic therapies in order to minimize the high cost of therapies (181).…”
Section: Genito-urinary Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of multi-drug resistance has led doctors to look for milder prophylactic therapies in order to minimize the high cost of therapies (181).…”
Section: Genito-urinary Infectionsmentioning
confidence: 99%
“…Probiotic effects on urinary tract infections remain controversial ( 181 – 183 ) ( Table 6 ). While a team states that there is no benefit from probiotics administration ( 182 ), other scientists observe a shortening of the average duration of illness, as well as a considerable reduction of the infection rate ( 181 , 184 ).…”
Section: Genito-urinary Infectionsmentioning
confidence: 99%
“…Although there have been few studies on the determentof RUTIs without use of antibiotics within the past years, interest probiotics has increased over the years. Reviews by Akgül et.al, 2018 concluded that evidence of probiotic appliancein UTIs is not yet sufficient to recommend use of probiotics [316]. Different vaccines based on the whole cells (killed or live-attenuated vaccines) and antigens (subunits, toxins and conjugated vaccines) have been evaluated against UTIs pathogens, as reported by Asadi et.al, 2019 [317].…”
Section: Recurrent Urinary Tract Infectionsmentioning
confidence: 99%
“…stressful life [438], urban living, mastectomy [439], lower socioeconomic status [435], [440], genetic predisposition, African-American origin, not having children or breastfeeding, early menstruation/ late menopause, obesity, alcohol abuse, HRT after menopause, benign breast conditions or having breast proliferation, using contraceptives and exposure to diethylstilbestrol [441], age between 40-60, late age first pregnancy, smoking [442], abortion history [443] are the associated factors. Distressingly, the 5-year cumulative mortality remains unacceptably high at 50%, primarily due to a late-stage presentation [316]. Wearing bra is not associated with breast cancer risk [443] but wearing (tight) bras for many hours and having breast implants [442], [445] may have associations.…”
Section: C) Breast Cancermentioning
confidence: 99%
“…DOI: http://dx.doi.org/10.17352/jgro.000068excellent results in terms of effi cacy and 60.3% and 39.7% rated as excellent and good in terms of safety profi le respectively.DiscussionUrogenital infections not caused by sexual transmission, namely yeast vaginitis, bacterial vaginosis, and urinary tract infection remain a major medical problem in terms of the number of women affl icted each year[7].When vaginal fl ora is examined, it is known that microorganisms of Lactobacillus spp. are dominant bacteria and form urinary microbiota which demonstrates antimicrobial activity[8].Recurrence rate of BV remains high with use of antimicrobials and such treatments are not designed to restore the lactobacilli. Antimicrobial drug resistance remains a root cause for BV recurrence [9].…”
mentioning
confidence: 99%